Reoperation Rates After Combined Anterior Cruciate Ligament and Anterolateral Ligament Reconstruction: A Series of 548 Patients From the SANTI Study Group With a Minimum Follow-up of 2 Years. (September 2017) - Thaunat, Mathieu; Clowez, Gilles; Saithna, Adnan; Cavalier, Maxime; Choudja, Eric; Vieira, Thais D.; Fayard, Jean-Marie; Sonnery-Cottet, Bertrand
Background: Early clinical results of anterolateral ligament (ALL) reconstruction are promising, but concerns exist due to high rates of complications after other types of lateral extra-articular tenodesis. The rate of surgery after combined anterior cruciate ligament (ACL) and ALL reconstruction is not known. Purpose: To determine the rate of reoperation after combined ACL and ALL reconstruction. Study Design: Case series; Level of evidence, 4. Methods: A retrospective analysis of prospectively collected data from the Scientific ACL Network International (SANTI) Study Group database was performed to include all patients who had undergone combined ACL and ALL reconstruction between January 2012 and June 2014. At the end of the study period, all patients were contacted by telephone, and the operative notes of those who stated that they had undergone reoperation were reviewed to determine the type and rates of the subsequent procedures performed. Descriptive data were analyzed for the entire patient cohort. Results: The study population comprised 548 quadruple hamstring graft (4HT)+ALL reconstructions. The mean age (±SD) was 24.3 ± 7.9 years (range, 11.9-55.7 years), and 70.3% of subjects were male. The mean duration of follow-up was 35.5 ± 8.0 months (range, 24-54 months). Seventy-two patients (13.1%) underwent ipsilateral reoperation. This comprised a total of 77 procedures. Graft revision occurred in 14 knees (2.6%) at a mean of 18.3 months (±7.4 months) after the index procedure. There were 63 reoperations for ipsilateral, non–graft rupture–related indications (meniscus, n = 30; arthrofibrosis, n = 22; removal of hardware, n = 4; deep infection, n = 3; arthroscopic lavage without infection, n = 4). The only specific complications related to the ALL procedure (n = 3) were all related to femoral hardware that required removal. In both univariate and multivariate analyses, only the presence of a medial meniscal lesion at the index procedure was significantly associated with ipsilateral reoperation (odds ratio, 2.58; 95% CI, 1.43-4.76; P = .002). Conclusion: The reoperation rate after combined ACL and ALL reconstruction in this series is broadly comparable to the reoperation rate after isolated ACL reconstruction as reported in previous studies. In addition, the high rates of knee stiffness and reoperation reported in historical series of nonanatomic, lateral extra-articular tenodesis were not observed in the current series.